To the study of the species composition of coccidia (Sporozoa, Eucoccidiida) of the gray rat (Rattus norvegicus) from different regions of Azerbaijan - Gurbanova, T. F.; Mamedova, S. O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
In the feces of gray rat (Rattus norvegicus) caught in buildings of Qakh district and Baku city the oocysts of Cryptosporidium and Eimeria (Apicomplexa, Sporozoa, Eucoccidiida) were found. The Cryptosporidium oocysts of gray rats caught in Qakh district and Baku city, by their morphometric characters were similar with C. muris Tyzzer, 1907, C. parvum Tyzzer, 1912. Eimeria oocysts observed in Qakh district are proved to be E. miyairii Ohira, 1912 (= E. nieschulzi Dieben, syn. E. halli Yakimoff, 1935, 1924, syn. E. carini Pinto, 1928). Eimeria oocysts observed in urban population of rats by their morphometric parameters were different from all previously described species of Eimeria parasitizing in rats.